2021
DOI: 10.53682/jpjsre.v2i1.1320
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Masyarakat Kelurahan Pinokalan Dalam Pelaksanaan Program Kota Tanpa Kumuh (Kotaku) Di Kelurahan Pinokalan Kota Bitung Sulawesi Utara

Abstract: The problem in this study is about the perception of pinokalan village community regarding the assistance of Kota Tanpa Kumuh Program (KOTAKU) where they are concerned about the inability of the opportunity to receive this assistance and the purpose of this research is to know and describe the perception of pinokalan village community in the implementation of KOTAKU program. In this study using qualitative research method with observation and interview data collection techniques. And the results of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research that is relevant to this research is the research of Audrey et al [3] the results of this study show that the perception of the people of Pinokalan Village where they don't know much about the Kotaku program. This may be due to lack of socialization or inappropriate socialization advice.…”
Section: Introductionmentioning
confidence: 81%
“…Research that is relevant to this research is the research of Audrey et al [3] the results of this study show that the perception of the people of Pinokalan Village where they don't know much about the Kotaku program. This may be due to lack of socialization or inappropriate socialization advice.…”
Section: Introductionmentioning
confidence: 81%
“…Other research on community response with the aim of influencing community responses to the Kotaku Program in Pekanbaru City, found a positive effect and significance of the response (Afdillah, 2021). Then, other research on people's perceptions of the Kotaku program in Bitung City, North Sulawesi, found results that the community had difficulties and were not used to running the program (Runtukahu et al, 2021). Research on the Kotaku program's Clean Water Facilities (SAB) in Mekarsari and Pasirsari Villages had never been done before, so in this study the researchers wanted to know the community's response to Clean Water Facilities activities, in two villages by using the criteria of efficiency, effectiveness and sustainability.…”
Section: Introductionmentioning
confidence: 99%